2022
DOI: 10.1111/raq.12709
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA, a supreme post‐transcriptional immune regulator of bacterial or virus‐driven immune evolution in teleost

Abstract: The global aquaculture boom, fuelled by a reduction in wild population and detection of novel viruses, has created a demanding market, hence, there is a pressing need to investigate the immune system of fish, further. As the most diverse community of vertebrates and a central contributor to the progressing global aquaculture market, teleost continues to draw vast scientific interest. Recent breakthroughs in multiomics technologies have provided a platform to understand the role of long noncoding RNA (lncRNA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 168 publications
(275 reference statements)
0
2
0
Order By: Relevance
“…In addition to protein-coding genes, long-noncoding RNA (lncRNAs) are RNA molecules with a length of over 200 nt that possess various functions in regulating gene transcription, epigenetic regulation, and cell proliferation and differentiation (Esteller 2011 ; Chen et al 2022 ). Recently, several studies have investigated the roles of lncRNAs in the immunity of fish (Wang et al 2018 ; Leiva et al 2020 ; Zheng et al 2021a ; Haridevamuthu et al 2023 ). Zheng et al ( 2022 ) demonstrated that the lncRNA MIR122HG inhibits the innate immune response by negatively regulating the TAK1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protein-coding genes, long-noncoding RNA (lncRNAs) are RNA molecules with a length of over 200 nt that possess various functions in regulating gene transcription, epigenetic regulation, and cell proliferation and differentiation (Esteller 2011 ; Chen et al 2022 ). Recently, several studies have investigated the roles of lncRNAs in the immunity of fish (Wang et al 2018 ; Leiva et al 2020 ; Zheng et al 2021a ; Haridevamuthu et al 2023 ). Zheng et al ( 2022 ) demonstrated that the lncRNA MIR122HG inhibits the innate immune response by negatively regulating the TAK1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In such approach, role of lncRNA-miRNA-mRNA axis has immense impact on aquaculture productivity, fish health, and quality ( Zhou et al, 2023 ). Besides this, lncRNA has key role in immunity of fish which is directly linked with productivity ( Haridevamuthu et al, 2023 ). Aquaculture is currently considered essential in ensuring food security and maintaining economic stability, and it is the most rapidly expanding farmed food industry on a global scale due to the depletion of natural fish populations ( Jennings et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%